THE INFLUENCE OF TECHNOPRENEURSHIP SCIENTIFIC LEARNING, AND PRIOR KNOWLEDGE TOWARDS ABILITY TO IDENTIFY ENTREPRENEURIAL OPPORTUNITIES - Hidayat, Hendra; Herawati, Susi; Syahmaidi, Eril; Hidayati, Abna (PEOPLE: International Journal of Social Sciences, 2020)
The low prior knowledge of entrepreneurship and learning that is not interesting and boring is assumed to have an impact on the ability to identify entrepreneurial opportunities in Technical and Vocational Education Students. The purpose of this research is to describe and test the influence of Technopreneurship Scientific Learning, and Prior Knowledge Towards the Ability to Identify Entrepreneurial Opportunities. This research uses quantitative methods with descriptive correlational. The population is all students who take entrepreneurship courses in Higher Education as many as 300 people, and a sample of 150 students is selected using proportional random sampling. This research tool is a Likert scale that has been measured for validity and reliability. Data were analyzed using multiple regression. The research findings show that there is an influence of Technopreneurship Scientific Learning and Prior Knowledge together on the Ability to Identify Entrepreneurial Opportunities in Technical and Vocational Education Students